2022
DOI: 10.1162/neco_a_01485
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Computational Demands Underlying Visual Reasoning

Abstract: Visual understanding requires comprehending complex visual relations between objects within a scene. Here, we seek to characterize the computational demands for abstract visual reasoning. We do this by systematically assessing the ability of modern deep convolutional neural networks (CNNs) to learn to solve the synthetic visual reasoning test (SVRT) challenge, a collection of 23 visual reasoning problems. Our analysis reveals a novel taxonomy of visual reasoning tasks, which can be primarily explained by both … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…In contrast, both models only achieved acceptable performance on the rectangles dataset and poor performance on the straight lines, connected squares and connected circles datasets in the same-different task. This marked difference in task generalization is consistent with previous results by Kim et al (2018) ; see also Vaishnav et al (2021) , who reported that visual reasoning tasks that involve same-different judgments are more difficult for CNNs than other spatial reasoning tasks. Furthermore, these results provide further support to the idea that DCNNs do not form abstract representations of the relations same and different when trained on the same-different task.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, both models only achieved acceptable performance on the rectangles dataset and poor performance on the straight lines, connected squares and connected circles datasets in the same-different task. This marked difference in task generalization is consistent with previous results by Kim et al (2018) ; see also Vaishnav et al (2021) , who reported that visual reasoning tasks that involve same-different judgments are more difficult for CNNs than other spatial reasoning tasks. Furthermore, these results provide further support to the idea that DCNNs do not form abstract representations of the relations same and different when trained on the same-different task.…”
Section: Resultssupporting
confidence: 91%
“…Bowers et al argue that the inability of DNNs to learn human-like visual strategies reflects architectural limitations. They are correct that there is a rich literature demonstrating how mechanisms inspired by neuroscience can improve the capabilities of DNNs, helping them learn perceptual grouping (Kim, Linsley, Thakkar, & Serre, 2020;Linsley, Kim, Ashok, & Serre, 2019a;Linsley, Kim, Veerabadran, Windolf, & Serre, 2018, visual reasoning (Kim, Ricci, & Serre, 2018;Vaishnav et al, 2022;Vaishnav & Serre, 2023), robust object recognition (Dapello et al, 2020), and to more accurately predict neural activity Kubilius et al, 2018;Nayebi et al, 2018). The other fundamental difference between DNNs and biological organisms is how they learn; humans and DNNs learn from vastly different types of data with presumably different objective functions.…”
Section: The Next Generation Of Dnns For Biological Visionmentioning
confidence: 99%
“…Note, however, that overall generalization performance was far from optimal. Previous research on the visual reasoning capabilities of DNNs has focused heavily on the same-different task (Adeli, Ahn and Zelinsky, 2023b;Baker, Garrigan, Phillips and Kellman, 2023;Funke, Borowski, Stosio, Brendel, Wallis and Bethge, 2021;Kim, Ricci and Serre, 2018;Falchi, 2021, 2022;Puebla and Bowers, 2022;Ricci et al, 2021;Stabinger, Peer and Rodríguez-Sánchez, 2021;Tartaglini, Feucht, Lepori, Vong, Lovering, Lake and Pavlick, 2023;Vaishnav, Cadene, Alamia, Linsley, VanRullen and Serre, 2022;Webb, Mondal and Cohen, 2023c;Webb, Sinha and Cohen, 2021). This is due to the fact that the concept of sameness is considered to be fundamental to human thought (Hochmann, Wasserman and Carey, 2021), develops early in human infants (Hespos, Gentner, Anderson and Shivaram, 2021), and it is more sophisticated in humans in comparison to other species (Gentner, Shao, Simms and Hespos, 2021).…”
Section: Introductionmentioning
confidence: 99%